2010
DOI: 10.1179/174329409x409521
|View full text |Cite
|
Sign up to set email alerts
|

Erosion properties of Fe based amorphous/nanocrystalline coatings prepared by wire arc spraying process

Abstract: Fe-Cr-B-Si-Mn-Nb-Y and Fe-B-Si-Nb-Cr amorphous/nanocrystalline coatings were fabricated by wire arc spray process. The microstructure and phase compositions of the coatings were characterised by means of SEM, EDAX and XRD. The formation mechanism of amorphous phase and nanocrystalline phase was discussed. The elevated temperature erosion behaviour of the coatings was also investigated using an air solid particle erosion rig. The microstructures of the coatings consist of amorphous phase and a-(Fe,Cr) nanocryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…It provides superior hardness and abrasion strength to the material because of its high carbide production features. Some researchers have worked with Fe-based arc spray coating wire, including Fe-Cr alloy, 30 FeCrCMn, 31 Fe-Cr-Al-B, 32 Fe-C-Cr alloy, 33,34 FeBSiNb, 35 FeCrBSiMnNbY and FeBSiNbCr, 36 and FeCrB(CSi) and Fe-Cr-Al. 37 Basic advantages including subdued cost, elevated spray rate, high deposit capacity, ease of application, and elasticity are the main reasons for the widespread use of the EAS technique.…”
Section: Introductionmentioning
confidence: 99%
“…It provides superior hardness and abrasion strength to the material because of its high carbide production features. Some researchers have worked with Fe-based arc spray coating wire, including Fe-Cr alloy, 30 FeCrCMn, 31 Fe-Cr-Al-B, 32 Fe-C-Cr alloy, 33,34 FeBSiNb, 35 FeCrBSiMnNbY and FeBSiNbCr, 36 and FeCrB(CSi) and Fe-Cr-Al. 37 Basic advantages including subdued cost, elevated spray rate, high deposit capacity, ease of application, and elasticity are the main reasons for the widespread use of the EAS technique.…”
Section: Introductionmentioning
confidence: 99%
“…Inspection of failed components revealed that the failure process is corrosion initiated and then erosion dominant corrosion initiated layers are removed faster due to combination of factors like micro pitting, local cavitations and impulsive jet of water with sand erodents. [25][26][27][28][29] It was observed that WC-Co-Cr cermet coating deposited with fine grained WC exhibits higher slurry erosion resistance under all testing conditions as compared to conventional cermet coating.…”
Section: Other Influencing Factorsmentioning
confidence: 94%
“…In the case of nanocrystalline grain size, more than 50% of atoms are associated with grain boundaries due to small grain size resulting in more contribution towards physical properties of material [25]. Nanocrystalline coatings can be deposited using several techniques, yet thermal spraying has been reported by several researchers as one of the best techniques available [46][47][48][49][50][51][52][53][54][55]. Thermal spraying with nanostructured feedstock powders has resulted in higher hardness, strength, and corrosion resistance compared to conventional powders.…”
Section: Nanostructured Cermet Coatingsmentioning
confidence: 99%